PENGARUH TATA KELOLA PERUSAHAAN DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Safitri Putri Anjasari; Hastutie Noor Andriati (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2016)
This research aimed to examine the influence of corporate governance and environmental performance to firm value. Corporate governance was identified by the proportion of institusional ownership, the proportion of independent commissioner board, and number of audit committee. Firm value was proxied by Tobin’s Q (market-based financial performance), while environmental performance was measured by PROPER issued by the Indonesian State Ministry of Environmental. The study used 72 sample from a population of 152 manufacturing companies listed on Indonesian Stock Exchange in the period of 2013-2015. The sample was determined by using purposive sampling. The results showed that corporate governance mechanisms proxied by the proportion of independent commissioner board, and proportion of institusional ownership had effect on firm value, while the number of audit committee, and results proved nothing effect on firm value.Keywords: Corporate governance, environmental performance, firm value.